2021
DOI: 10.1016/j.jds.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Significantly higher serum tumor marker levels in patients with oral submucous fibrosis

Abstract: Background/purpose Our previous study showed that carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC–Ag), and ferritin are significantly higher in patients with oral potentially malignant disorders (OPMDs including oral leukoplakia, oral erythroleukoplakia, and oral verrucous hyperplasia) than in healthy controls (HCs). Oral submucous fibrosis (OSF) is also recognized as an OPMD. This study evaluated whether these three serum tumor marker levels were also significantly higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…In relation to OPMD, we observed statistical differences in ferritin and total proteins versus the control group. This is consistent with the findings of Wu et al [37,38], who recorded significantly higher levels of carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC-Ag) and ferritin in the serum of patients with oral precancer than in the healthy controls. Thus, serum CEA, SCC-Ag and ferritin may represent potential tumor markers for the detection of patients with oral precancerous lesions [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…In relation to OPMD, we observed statistical differences in ferritin and total proteins versus the control group. This is consistent with the findings of Wu et al [37,38], who recorded significantly higher levels of carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCC-Ag) and ferritin in the serum of patients with oral precancer than in the healthy controls. Thus, serum CEA, SCC-Ag and ferritin may represent potential tumor markers for the detection of patients with oral precancerous lesions [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that the blood levels of tumor markers are significantly higher in patients with malignant tumors than in healthy individuals [ 43 ].CEA is a glycoprotein located on the cell surface and is synthesized in early fetal life by the gastrointestinal tract, liver, and pancreas, and in adults, the epithelial tissue of the gastrointestinal tract and the liver and pancreas can also synthesize small amounts of CEA and secrete it into the digestive tract at low levels under normal conditions [ 44 ]. There have been many studies on CEA as a marker of oral and maxillofacial malignancies [ 45 , 46 ]. CEA has been found to be highly expressed in tumor tissues of patients with squamous cell carcinoma of the head and neck [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous associated studies, patients with serum CEA level ≥3 ng/mL, SCC-Ag level ≥2 ng/mL, and ferritin level ≥250 ng/mL were scored as serum positive for CEA, SCC-Ag, and ferritin, respectively. 21 , 22 , 23 , 24 , 27 , 28 , 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“… 19 , 20 Elevated serum SCC-Ag level and high serum SCC-Ag-positivity have also been found in oral cancer and oral precancer patients. 21 , 22 , 23 , 24 In addition, the serum ferritin represents the level of iron stored in human bodies, and many studies found that combination of serum ferritin and other biomarkers might be of great value in diagnosing some human cancers, including oral cancers. 25 , 26 Therefore, considering the potential of malignant transformation of OLP, we aimed to evaluate the serum levels of CEA, SCC-Ag, and ferritin in OLP patients and to assess whether there were significantly higher serum levels and positive rates of these three tumor biomarkers in OLP patients than in healthy control subjects in this study.…”
Section: Introductionmentioning
confidence: 99%